Identificação morfológica e molecular de fungos associados à podridão de manivas semente em variedades de mandioca no município de Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Studiesonphytopathogensassociatedwithroot rotincassavaarefrequent,unlikethestudyof fungi associated with stem rot in cuttings, which is the main means of propagation used by producers. The purpose was to isolate and morphologically and molecularly identify the main fungi in cassava stem rot. Five cassava varieties (Água morna, Amarelinha, BRS Kiriris, BRS Poti and São Paulo) from the regions of Eixo Forte and Planalto de Santarém-PA were evaluated. The material was divided into six rods of each variety, 15 cm long, of which three underwentsurfacedisinfection(1minuteinalcoholand4minutesin2%sodiumhypochlorite) and three were not disinfected, being placed in a humid chamber. for 30 days. The fungi were isolatedinPDAmediumwithamoxicillin,purifiedandthestructuresevaluatedbymicroscopy. DNAextractionwasperformedfromplateswithpurecolonies.AmplificationoftheITSregion with ITS1 and ITS4 primers and sent for sequencing. The sequences obtained were edited, contigs obtained and compared with the sequences deposited in Genbank by BLAST. The disinfectionprocesswasineffective,asinbothtreatmentstherewasgrowthoffungalstructures, butitindicatesthatphytopathogensmaybemicroorganismsofendophyticnature.Atotalof47 isolates were obtained: Warm water = 8 isolates; Little yellow = 8 isolates; Warm water - Plateau = 4 isolates; BRS Kiriris= 17 isolates; BRS Poti= 6 isolates; São Paulo= 4 isolates. In all varieties, frequent isolates were observed that, through microscopy, were identified at the genus level as: Lasiodiploidia, Aspergillus and Fusarium. From the sequences obtained, it revealedsimilarityofidentitywithA.japonicus,A.assiutensis,A.pseudonomius,F.solani,F. equiseti,Fusariumsp.,L.pseudotheobromae,L.theobromaeandL.brasiliensis.L.theobromae was the most frequent species, accordingto reports on cassava stem rot.Thegenera Fusarium andLasiodiplodiaaredescribedassomeofthoseresponsibleforcassavarootrot(dryandblack, respectively),aswellasotherdiseasesinothercrops.Thisworkdetectedthreegeneraoffungi associatedwithstemrotinthemunicipalityofSantarém,ofwhichtwoareassociatedwithroot rot.
Keywords: Mandioca; Podridão; Estacas; Propagação vegetal; fitopatógenos; CNPQ:: CIÊNCIAS BIOLÓGICAS